2016
DOI: 10.1126/science.aad8352
|View full text |Cite
|
Sign up to set email alerts
|

Conformational photoswitching of a synthetic peptide foldamer bound within a phospholipid bilayer

Abstract: The dynamic properties of foldamers, synthetic molecules that mimic folded biomolecules, have mainly been explored in free solution. We report on the design, synthesis, and conformational behavior of photoresponsive foldamers bound in a phospholipid bilayer akin to a biological membrane phase. These molecules contain a chromophore, which can be switched between two configurations by different wavelengths of light, attached to a helical synthetic peptide that both promotes membrane insertion and communicates co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
138
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 56 publications
1
138
0
1
Order By: Relevance
“…15,27,28 Recently, covalently controlled conformational switching over multi-nanometre distances within membrane-bound Aib foldamers was demonstrated using a light-switchable molecule. 29 The ligand binding pocket was constructed from a cationic metal(II) bis(2-quinolylmethyl)(2-pyridylmethyl)amine (BQPA) complex (Fig. 1a, "Input").…”
mentioning
confidence: 99%
“…15,27,28 Recently, covalently controlled conformational switching over multi-nanometre distances within membrane-bound Aib foldamers was demonstrated using a light-switchable molecule. 29 The ligand binding pocket was constructed from a cationic metal(II) bis(2-quinolylmethyl)(2-pyridylmethyl)amine (BQPA) complex (Fig. 1a, "Input").…”
mentioning
confidence: 99%
“…69,70 In fact, 87% stereocontrol could be recorded over 19 amino acid residues. Recently, the group has demonstrated that this form of information transfer could also be realized through a phospholipid bilayer, both by using a photoswitchable unit 71 and by binding a chiral ligand. As such, they prove that their design of a simplified analog for membrane spanning proteins may in fact be operated in the membrane.…”
Section: Biohybrid Systemsmentioning
confidence: 99%
“…In particular, of the many therapeutic peptides and proteins that have been discovered, only a few are in current use due to their low bioavailability and susceptibility to enzymatic degradation1516. Synthetic self-assembled capsules could mitigate these limitations by altering the solubility of peptides and protecting them from cleavage, following the example of previous successful interfaces between abiological and biological systems1718. However, the only examples of the encapsulation of such molecules reported to date involve the covalent, irreversible attachment of a protein to the inside of a cage, preventing release or exchange19, or the encapsulation of short peptides2021.…”
mentioning
confidence: 99%